Potential of silvo-pastoralism for adaptation and mitigation in the context of drylands - Louhaichi, Mounir (2024)
The presentation, given by Mounir Louhaichi during the "Potential of Dryland Silvopastoral Systems for Global Decarbonization Action" side event at COP 16 in KSA. The presentation explores the role of silvopastoral systems in drylands, which cover 41% of Earth's land surface and support a significant portion of global agriculture and livestock. Highlighting their potential for carbon sequestration (1-4 tons of CO₂ per hectare annually), the presentation discusses the ecological and economic benefits of integrating trees and grasses in livestock systems. It emphasizes the importance of sustainable management practices, participatory governance, and the need for educational initiatives to enhance the resilience of these ecosystems against climate change impacts.